(untitled) (Kajian Ilmiah Mahasiswa Administrasi Publik (KIMAP), 2020)
This study purposed to determine the Government’s Supervision Strategy in the Management of Hazardous and Toxic (B3) waste Hotel in Makassar City. This study used a qualitative descriptive and phenomonological type. The results of this study showed that the Makassar City Environment Department has the main task of formulating, fostering, coordinating and controlling policies in the environmental field including environmental impact analysis, environmental impact recovery and environmental law compliance. In addition, the government’s supervision strategy in managing hotel B3 waste in Makassar City, the Office of the Environment had not been maximized in controlling B3 waste management by considering determinant factors, including inadequate facilities and infrastructure and the lack of understanding of B3 waste by the hotel.